1997
DOI: 10.1161/01.hyp.29.5.1204
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Anandamide in Anesthetized and Conscious Normotensive and Hypertensive Rats

Abstract: We previously showed that in anesthetized rats anandamide elicits bradycardia and a triphasic blood pressure response: transient hypotension secondary to a vagally mediated bradycardia, followed by a brief pressor and prolonged depressor response, the latter two effects being similar to those of delta 9-tetrahydrocannabinol (THC). The prolonged depressor but not the pressor response was reduced after alpha-adrenergic receptor blockade or cervical spinal cord transection and was inhibited by the cannabinoid typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
137
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 29 publications
15
137
2
Order By: Relevance
“…All of these findings indicate the absence of an endocannabinergic 'tone' in the maintenance of normal blood pressure. In contrast, both anandamide (Lake et al, 1997b;Bátkai et al, 2004a) and THC (Kosersky, 1978) evoke larger and longer lasting hypotension in SHR than in normotensive rats, and the effect in the former does not depend on the absence or presence of anesthesia (Lake et al, 1997b). Consistent with these observations, THC inhalation was found to result in a greater and longer lasting decrease of arterial blood pressure in hypertensive as compared to normotensive individuals (Crawford and Merritt, 1979).…”
Section: Role Of the Endocannabinergic System In Blood Pressure Regulmentioning
confidence: 83%
See 2 more Smart Citations
“…All of these findings indicate the absence of an endocannabinergic 'tone' in the maintenance of normal blood pressure. In contrast, both anandamide (Lake et al, 1997b;Bátkai et al, 2004a) and THC (Kosersky, 1978) evoke larger and longer lasting hypotension in SHR than in normotensive rats, and the effect in the former does not depend on the absence or presence of anesthesia (Lake et al, 1997b). Consistent with these observations, THC inhalation was found to result in a greater and longer lasting decrease of arterial blood pressure in hypertensive as compared to normotensive individuals (Crawford and Merritt, 1979).…”
Section: Role Of the Endocannabinergic System In Blood Pressure Regulmentioning
confidence: 83%
“…Treatment of normotensive rats or mice with CB 1 antagonists alone was found not to affect blood pressure (Lake et al, 1997a;Varga et al, 1995), and baseline blood pressure was similar in CB 1 knockout mice and their wild-type littermates (Járai et al, 1999;Ledent et al, 1999). Further studies demonstrated that a relatively modest hypotensive effect of anandamide was present in anesthetized (Lake et al, 1997a;Varga et al, 1995) but not in conscious normotensive rats (Stein et al, 1996;Lake et al, 1997b), and a lack of significant hypotension following inhibition of anandamide transport (Calignano et al, 1997). All of these findings indicate the absence of an endocannabinergic 'tone' in the maintenance of normal blood pressure.…”
Section: Role Of the Endocannabinergic System In Blood Pressure Regulmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The hypotensive potency of a series of agonists, including those tested in the present study, displayed a strong positive correlation with their analgesic potency or their binding K d to the brain cannabinoid receptor. 22 Furthermore, the inhibitory potency of the highly selective CB1 receptor antagonist SR141716A 23 was similar for cannabinoid-induced hypotension 33 and neurobehavioral effects. 23 Although SR141716A did inhibit the mesenteric vasodilator response to anandamide, the inhibition was unusual in that a 10-fold increase in the concentration of the antagonist resulted in a much smaller than expected increase in inhibition.…”
Section: Discussionmentioning
confidence: 93%
“…In rats, intravenous administration of anandamide, an endogenous cannabinoid primarily acting on the CB1 receptor, has been found to have a triphasic effect on blood pressure, characterized by a transient drop followed by a brief rise and then a sustained period of hypotension. 5,6 The human cardiovascular system appears to be affected by THC. A placebo-controlled trial showed that, among people who used cannabis regularly, systolic blood pressure dropped with an oral THC dose of 30 mg but increased at doses greater than 75 mg. 7 A concomitant dosedependent elevation in heart rate was noted.…”
Section: Discussionmentioning
confidence: 99%